Hubungan Lingkungan Fisik dan Kebiasaan Keluarga dengan Kejadian DBD - Poene, Diana Claudia; Toar, Jilly; Bawiling, Nancy S. (Jurnal Ilmiah Kesehatan, 2025)
Dengue Hemorrhagic Fever (DBD) is a disease caused by the dengue virus through the bite of Aedes mosquitoes, especially Aedes aegypti. The purpose of this study is to determine the Relationship Between Physical Environment and Family Habits with DBD Incidence in the Working Area of Puskesmas Tikala Baru Year 2025. The method in this study used a quantitative method with case control design. The research sample was 128 respondents consisting of 64 cases and 64 controls, tested using chi-square. The results of this study showed relationships between physical environment and family habits with DBD incidence: availability of covers on water containers (p=0.028; OR=0.370), open drainage channels (p<0.001; OR=9.178), presence of used goods (p<0.001; OR=20.810), land availability for burying used goods (p=0.008; OR=0.354), cleaning water containers weekly (p<0.001; OR=0.069), use of mosquito repellent (p=0.049; OR=0.459), hanging clothes (p<0.001; OR=0.223), and presence of larvae in water containers (p<0.001; OR=6.576). No relationships were found in the use of mosquito nets, mosquito wire screens, and the habit of recycling used goods.